Social preferences, beliefs, and the dynamics of free riding in public good experiments - Urs Fischbacher; Simon Gächter (Center for Economic Studies and ifo Institute (CESifo), 2008)
We provide a test of the role of social preferences and beliefs in voluntary cooperation and its decline. We elicit individuals' cooperation preferences in one experiment and use them as well as subjects' elicited beliefs to explain contributions to a public good played repeatedly. We find substantial heterogeneity in people' preferences. With simulation methods based on this data, we show that the decline of cooperation can be driven by the fact that most people have a preference to contribute less than others, rather than by their changing beliefs of others' contribution over time. Universal free riding is very likely despite the fact that most people are not selfish.
Keywords: C91; C72; H41; D64; 330; Public goods experiments; social preferences; conditional cooperation; free riding; Trittbrettfahrerverhalten; Öffentliches Gut; Test; Soziale Wohlfahrtsfunktion; Kooperation; Theorie